L'eau et ses enjeux - Anctil, François (Presse de l'Université Laval, 2016)
Avec L'eau et ses enjeux, nous suivons le cycle de l'eau avec une rigueur scientifique tout en observant de manière critique les actions humaines pour s'approvisionner. Le résultat est éclairant. La 2e édition a été revue et augmentée.
Keywords: Ouvrage_Collectif_Numéro1

Forcing the Penman-Montheith Formulation with Humidity, Radiation, and Wind Speed Taken from Reanalyses, for Hydrologic Modeling - Ricard, Simon; Anctil, François (Water, 2019)
The Penman-Monteith reference evapotranspiration (ET0) formulation was forced with humidity, radiation, and wind speed (HRW) fields simulated by four reanalyses in order to simulate hydrologic processes over six mid-sized nivo-pluvial watersheds in southern Quebec, Canada. The resulting simulated hydrologic response is comparable to an empirical ET0 formulation based exclusively on air temperature. However, Penman-Montheith provides a sounder representation of the existing relations between evapotranspiration fluctuations and climate drivers. Correcting HRW fields significantly improves the hydrologic bias over the pluvial period (June to November). The latter did not translate into an increase of the hydrologic performance according to the Kling-Gupta Efficiency (KGE) metric. The suggested approach allows for the implementation of physically-based ET0 formulations where HRW observations are insufficient for the calibration and validation of hydrologic models and a potential reinforcement of the confidence affecting the projection of low flow regimes and water availability.

Impacts of precipitation on the cryologic regime of stream channels - Turcotte, Benoit; Morse, Brian; Anctil, François (Hydrological Processes, 2012)
Abstract This paper examines the controlling influence of snow and rain on river ice processes in creeks and streams. Winter precipitation (in the form of rain and snow) has been observed to affect river ice processes and channel parameters of low and high gradient channels in unsuspected ways that can have significant impacts on channel hydraulics, hydrology and habitat. On a low gradient stream, a snowfall event initiated the development of an ice cover by creating unconsolidated snow slush bridges that eventually froze in place. Afterward, both snowfalls and rainfalls in alternation with cold spells dramatically increased the thickening rate of the ice cover well beyond that predicted by classic equations. In a smaller low‐gradient agricultural creek, wind‐blown snow impeded the formation of an ice cover by insulating the flow from cold atmospheric conditions. On steep channels (of different sizes and morphologies), anchor snow slush has been seen to accumulate on the bed substrate. As opposed to anchor ice, anchor snow slush is not believed to require supercooling water conditions to form nor to stay in place. Finally, in a steep headwater creek, a rain‐on‐snow event generated a snow slush flow and multiple snow slush jams. This phenomenon was seen to divert most of the water out of the channel into another watershed and concomitantly signalled a mid‐winter breakup in the greater watershed downstream. These observations suggest that the role of precipitation on small channel winter ice morphology and water flows, levels and currents has been severely underestimated and that any ecological winter studies, hydraulic structure designs and river modelling efforts need to include processes that are sometimes dominated by rain, slush and snow. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

Hydrologie: cheminements de l'eau - Anctil, François; Rousselle, Jean; Lauzon, Nicolas (Presses internationales Polytechnique, 2012)
La quatrième de couverture indique : "L'hydrologie est la science qui étudie les eaux terrestres, leur origine, leur mouvement et leur répartition sur notre planète, leurs propriétés physiques et chimiques, leurs interactions avec l'environnement physique et biologique, et leur influence sur les activités humaines. Au sens plus strict, c'est la science qui étudie le cycle de l'eau dans la nature. Elle examine la distribution géographique et temporelle de l'eau dans l'atmosphère, en surface et dans le sol et le-sous-sol. Hydrologie - Cheminements de l'eau, deuxième édition, permet à l'hydrologue moderne d'explorer les volets scientifique et technique de l'hydrologie. Une description scientifique des phénomènes hydrologiques est offerte afin de proposer une motivation à leur étude, d'identifier les observations requises et d'assurer une compréhension de chaque étape du cycle de l'eau. Les éléments de chacune des situations d'apprentissage sont intégrés dans des modèles théoriques et d'application, et de nombreuses méthodes et techniques pour la résolution de problèmes hydrologiques sont présentées. En plus de fournir une description universelle de l'hydrologie, il couvre de multiples sujets dont l'estimation statistique des débits, l'exploitation des eaux, les systèmes d'information géographique et la télédétection. Il comporte, en outre, de nombreuses figures qui permettent d'en illustrer le propos, une bibliographie substantielle et quelque cent cinquante exercices. Ce livre s'adresse particulièrement aux étudiants de premier cycle universitaire en génie civil, forestier ou agricole, ainsi qu'à ceux de géographie physique, de géologie ou des sciences de l'environnement, mais aussi aux ingénieurs-conseils, au personnel des agences gouvernementales confronté à différents aspects de l'hydrologie et aux professeurs."

Accounting for three sources of uncertainty in ensemble hydrological forecasting - Thiboult, Antoine; Anctil, François; Boucher, Marie-Amélie (Hydrology and Earth System Sciences, 2016)
Abstract. Seeking more accuracy and reliability, the hydrometeorological community has developed several tools to decipher the different sources of uncertainty in relevant modeling processes. Among them, the ensemble Kalman filter (EnKF), multimodel approaches and meteorological ensemble forecasting proved to have the capability to improve upon deterministic hydrological forecast. This study aims to untangle the sources of uncertainty by studying the combination of these tools and assessing their respective contribution to the overall forecast quality. Each of these components is able to capture a certain aspect of the total uncertainty and improve the forecast at different stages in the forecasting process by using different means. Their combination outperforms any of the tools used solely. The EnKF is shown to contribute largely to the ensemble accuracy and dispersion, indicating that the initial conditions uncertainty is dominant. However, it fails to maintain the required dispersion throughout the entire forecast horizon and needs to be supported by a multimodel approach to take into account structural uncertainty. Moreover, the multimodel approach contributes to improving the general forecasting performance and prevents this performance from falling into the model selection pitfall since models differ strongly in their ability. Finally, the use of probabilistic meteorological forcing was found to contribute mostly to long lead time reliability. Particular attention needs to be paid to the combination of the tools, especially in the EnKF tuning to avoid overlapping in error deciphering.
Keywords: Ouvrage_Collectif_Numéro1

Water budget, performance of evapotranspiration formulations, and their impact on hydrological modeling of a small boreal peatland-dominated watershed. - Isabelle, Pierre-Erik; Nadeau, Daniel F.; Rousseau, Alain N.; Anctil, François (Canadian Journal of Earth Sciences, 2018)
Peatlands occupy around 13% of the land cover of Canada, and thus play a key role in the water balance at high latitudes. They are well known for having substantial water loss due to evapotranspiration. Since measurements of evapotranspiration are scarce over these environments, hydrologists generally rely on models of varying complexity to evaluate these water exchanges in the global watershed balance. This study quantifies the water budget of a small boreal peatland-dominated watershed. We assess the performance of three evapotranspiration models in comparison with in situ observations and the impact of using these models in the hydrological modeling of the watershed. The study site (~1-km2) is located in the Eastern James Bay lowlands, Quebec, Canada. During summer 2012, an eddy flux tower measured evapotranspiration continuously, while a trapezoidal flume monitored streamflow at the watershed outlet. We estimated evapotranspiration with a combinational model (Penman), a radiation-based model (Priestle...
Keywords: Rousseau_Alain

Comparing global and local calibration schemes from a differential split-sample test perspective - Gaborit, Étienne; Ricard, Simon; Lachance-Cloutier, Simon; Anctil, François; Turcotte, Richard (Canadian Journal of Earth Sciences, 2015)
This work explores the performances of the hydrologic model Hydrotel, applied to 36 catchments located in the Province of Quebec, Canada. A local calibration (each catchment taken individually) scheme and a global calibration (a single parameter set sought for all catchments) scheme are compared in a differential split-sample test perspective. Such a methodology is useful to gain insights on a model’s skills under different climatic conditions, in view of its use for climate change impact studies. The model was calibrated using both schemes on five non-continuous dry and cold years and then evaluated on five dissimilar humid and warm years. Results indicate that, as expected, local calibration leads to better performances than the global one. However, global calibration achieves satisfactory simulations while producing a better temporal robustness (i.e., model transposability to periods with different climatic conditions). Global calibration, in opposition to local calibration, thus imposes spatial consis...